Comparing Early Eukaryotic Integration of Mitochondria and Chloroplasts in the Light of Internal ROS Challenges: Timing is of the Essence - Speijer, Dave; Hammond, Michael; Lukeš, Julius (mBio, 2020)
When trying to reconstruct the evolutionary trajectories during early eukaryogenesis, one is struck by clear differences in the developments of two organelles of endosymbiotic origin: the mitochondrion and the chloroplast. From a symbiogenic perspective, eukaryotic development can be interpreted as a process in which many of the defining eukaryotic characteristics arose as a result of mutual adaptions of both prokaryotes (an archaeon and a bacterium) involved. This implies that many steps during the bacterium-to-mitochondrion transition trajectory occurred in an intense period of dramatic and rapid changes. In contrast, the subsequent cyanobacterium-to-chloroplast development in a specific eukaryotic subgroup, leading to the photosynthetic lineages, occurred in a full-fledged eukaryote. The commonalities and differences in the two trajectories shed an interesting light on early, and ongoing, eukaryotic evolutionary driving forces, especially endogenous reactive oxygen species (ROS) formation. Differences between organellar ribosomes, changes to the electron transport chain (ETC) components, and mitochondrial codon reassignments in nonplant mitochondria can be understood when mitochondrial ROS formation, e.g., during high energy consumption in heterotrophs, is taken into account.IMPORTANCE The early eukaryotic evolution was deeply influenced by the acquisition of two endosymbiotic organelles - the mitochondrion and the chloroplast. Here we discuss the possibly important role of reactive oxygen species in these processes.
Keywords: mitochondria; Reactive Oxygen Species; Cyanobacteria; Mitochondria; Time Factors; reactive oxygen species; biologická evoluce; chloroplasty; mitochondrie; Biological Evolution; chloroplast; sinice; Eukaryota; eukaryogenesis; reaktivní formy kyslíku; časové faktory; Chloroplasts